Perioperative Management of Patient with Systemic Mastocytosis Going for Total Thyroidectomy - Ammar AlShaker; Saud Al-Rasheedi; Yousef Al-Jebrin; Munira Al-Masaad; Nawaf M. Al-Mutairi (The Journal of Medicine, Law & Public Health)
Systemic mastocytosis (SM) is a rare disorder affecting 1 in 10,000 individuals, characterised by abnormal mast cell proliferation in extra-cutaneous organs, resulting in a variety of presentations ranging from mild asymptomatic disease to life-threatening tissue-destructive disease. Severe anaphylaxis caused by the release of histamine from mast cells can lead to poor postoperative outcomes, especially during general anaesthesia, as the severe manifestations of anaphylaxis, such as cardiovascular collapse and bronchospasm, may potentially be the first symptoms to present. In this case report, we describe the perioperative and intraoperative management of a 70-year-old female with SM, undergoing total thyroidectomy.